Chemically Crosslinked Hydrogel Film Leads to Integrated Flexible Supercapacitors with Superior Performance - Wang, Kai (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.